2015
DOI: 10.1007/s10482-015-0631-z
|View full text |Cite
|
Sign up to set email alerts
|

Microvirga makkahensis sp. nov., and Microvirga arabica sp. nov., isolated from sandy arid soil

Abstract: The taxonomic positions of two Gram-negative strains, SV1470(T) and SV2184P(T), isolated from arid soil samples, were determined using a polyphasic approach. Analysis of the 16S rRNA gene and the concatenated sequences of three housekeeping gene loci (dnaK, rpoB and gyrB) confirmed that the strains belong to the genus Microvirga. Strain SV1470(T) was found to be closely related to Microvirga vignae BR3299(T) (98.8 %), Microvirga flocculans TFB(T) (98.3 %) and Microvirga lupini Lut6(T) (98.2 %), whilst similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Microvirga colonies were pink in color after 8 days in YMA, as has been observed for other Microvirga strains, such as M. subterranea (20), M. lupini (15), and M. makkahensis (22). The growth rates of bradyrhizobial isolates from groups III and IV were similar to those of B. valentinum and B. retamae, respectively, with an extra-low growth rate phenotype on YMA plates.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Microvirga colonies were pink in color after 8 days in YMA, as has been observed for other Microvirga strains, such as M. subterranea (20), M. lupini (15), and M. makkahensis (22). The growth rates of bradyrhizobial isolates from groups III and IV were similar to those of B. valentinum and B. retamae, respectively, with an extra-low growth rate phenotype on YMA plates.…”
supporting
confidence: 71%
“…from arid and semiarid alkaline deserts, also in northern China (54). Since Microvirga strains have also been found in arid soils from other areas (22), the capacity to proliferate in arid soils may be an important feature of the symbiosis between Microvirga and L. micranthus in the semiarid soils of Tunisia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the taxonomic status of the L. cosentinii-isolated strains, phylogenetic trees based on the housekeeping concatenated 16S rRNA, dnaK, gyrB and recA sequences were built. The sequences of those genes have been used previously for identification of Microvirga (Ardley et al 2012;Radl et al 2014;Veyisoglu et al 2016;Msaddak et al 2017aMsaddak et al , 2017bRejili et al 2019). The results showed that the isolates from L. cosentinii belong to genus Microvirga and that LmiE10 and LmiM8 isolated from L. micranthus are the closest relative strains based on phylogenies of housekeeping genes.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors obtained a collection of 43 isolates of L. luteus from the same region, out of which 41 belonged to the genus Bradyrhizobium and just two to Microvirga [26]. The genus Microvirga currently comprises eighteen species [1,4,11,13,20,21,27,30,33,34,[37][38][39], of which only four have been described as effective root nodule bacteria: M. lotononidis and M. zambiensis isolated from Listia angolensis nodules [4], M. lupini, from Lupinus texensis [4] and M. vignae from Vigna unguiculata [27]. Through in-depth analysis of genetic, genomic and phenotypic data, we show here that Microvirga strains isolated from the root nodules of Northern Tunisian L. micranthus and L. luteus plants are representatives of a new symbiotic species that we propose to designate as Microvirga tunisiensis.…”
Section: Introductionmentioning
confidence: 99%